Dietary thiols in exercise: oxidative stress defence, exercise performance, and adaptation. Issue 1 (27th April 2017) - McLeay, Yanita; Stannard, Stephen; Houltham, Stuart; Starck, Carlene
Abstract: Endurance athletes are susceptible to cellular damage initiated by excessive levels of aerobic exercise-produced reactive oxygen species (ROS). Whilst ROS can contribute to the onset of fatigue, there is increasing evidence that they play a crucial role in exercise adaptations. The use of antioxidant supplements such as vitamin C and E in athletes is common; however, their ability to enhance performance and facilitate recovery is controversial, with many studies suggesting a blunting of training adaptations with supplementation. The up-regulation of endogenous antioxidant systems brought about by exercise training allows for greater tolerance to subsequent ROS, thus, athletes may benefit from increasing these systems through dietary thiol donors. Recent work has shown supplementation with a cysteine donor (N-acetylcysteine; NAC) improves antioxidant capacity by augmenting glutathione levels and reducing markers of oxidative stress, as well as ergogenic potential through association with delayed fatigue in numerous experimental models. However, the use of this, and other thiol donors may have adverse physiological effects. A recent discovery for the use of a thiol donor food source, keratin, to potentially enhance endogenous antioxidants may have important implications for endurance athletes hoping to enhance performance and recovery without blunting training adaptations.